Impact of living alone on the care and outcomes of patients with ST-elevation myocardial infarction. Issue 6 (June 2020) - Ohama, Ayumi; Mizuguchi, Yukio; Hashimoto, Sho; Yamada, Takeshi; Taniguchi, Norimasa; Nakajima, Shunsuke; Hata, Tetsuya; Takahashi, Akihiko
Highlights: ST-segment elevation myocardial infarction (STEMI) patients living alone tended to arrive late to the hospital. The onset-to-balloon times were shorter in STEMI patients living alone. Left ventricular ejection fraction was lower in STEMI patients living alone. Abstract: Background: This study aimed to investigate the association between living alone at home and the care and outcomes of patients with ST-segment elevation myocardial infarction (STEMI) who underwent primary percutaneous coronary intervention (pPCI). Methods: In total, 557 patients with STEMI underwent pPCI between January 2008 and September 2017. Among them, we included 208 patients who were transferred directly by emergency medical services from their home to the hospital. Results: Patients were classified into two groups, namely living alone (n = 45) and living with others (n = 163). There were no significant differences in age, sex, and cardiovascular risk factors between the two groups. The onset-to-door (OTD) and onset-to-balloon times were significantly shorter in patients living with others than in those living alone (106.4 vs. 190.8 min, p  < 0.01 and 152.3 vs. 236.9 min; p  < 0.01, respectively). The left ventricular ejection fraction after pPCI was significantly lower in patients living alone than in those living with others (48.7 % vs. 54.9 %, p  < 0.01). Multivariate logistic regression analysis indicated that living alone and the incidence of congestive heart failure were independent predictors of a longer OTD time. Conclusions: Patients living alone were less likely to arrive early at the hospital than those living with others. A greater understanding of the inter-relationships among living alone, access to acute cardiac care, and outcomes is essential.